Escobar Syndrome (Multiple Pterygium Syndrome) Associated with Thoracic Kyphoscoliosis, Lordoscoliosis, and Severe Restrictive Lung Disease: A Case Report - Dodson, Christopher C. (Springer-Verlag, 2005)
BACKGROUND: Escobar syndrome or multiple pterygium syndrome is characterized by a web across every flexion crease in the extremities, most notably the popliteal space. In addition, this syndrome is associated with two other structural anomalies: a vertical talus and congenital lordoscoliosis. We present a case report of a patient with Escobar syndrome who was initially managed conservatively and subsequently had severe and debilitating progression and respiratory decompensation ultimately requiring surgical intervention. STUDY DESIGN: Case report. METHODS: After preoperative evaluation by a pediatrician, pulmonologist, and otolaryngologist, the patient underwent one-stage anterior and posterior spinal fusion with instrumentation as well as multiple osteotomies, rib resections, and vertebrectomies. RESULTS: The patient’s postoperative course was complicated by wound necrosis requiring irrigation and debridement, a urinary tract infection, and a tracheostomy for persistent atelectasis. The patient eventually recovered from all complications. There were never any focal neurologic deficits. The patient had a 3-year follow-up with radiographically confirmed maintenance of correction. Fusion was obtained in the anterior and posterior segments. Clinically, the patient is able to stand upright, can participate in functional activities, and has not required any pain medication. The patient’s functional vital capacity improved from 23% predicted preoperatively to 60% predicted postoperatively. CONCLUSIONS: Patients with severe spinal deformity secondary to Escobar syndrome can be successfully treated surgically. We propose early surgical intervention in this group to prevent curve progression, restrictive lung disease, and the need for complex salvage procedures.